A naturalistic study assessing the impact of daytime running lights and vehicle passing events on cyclist's physiological stress. (December 2022) - Venkatachalapathy, Archana; Hamann, Cara; Spears, Steven; Shirtcliff, Elizabeth A.; Sharma, Anuj
Highlights: This study specifically targeted cyclists who expressed discomfort riding in traffic. Car passing events were observed to increase the cyclists' stress. Parked vehicles and roads with dashed centerline markings increased cyclists' stress. Daytime running lights had a negligible impact on cyclists' stress on roads. Separate bike facilities were associated with less cyclist stress than shared streets. Abstract: Bicyclists are vulnerable road users who are at a greater risk for injury and fatality during crashes. Additionally, the "near-miss" incidents they experience during regular trips can increase the perceived risk and deter them from riding again. This paper aims to use naturalistic bicycling data collected in Johnson County, Iowa to: 1) study the effect of factors such as road surface type, parked vehicles, pavement markings and car passing events on cyclists' physiological stress and 2) understand the effect of daytime running lights (DRL) as an on-bicycle safety system in providing comfort to cyclists and highlight of their presence on the road to other vehicles. A total of 37 participants were recruited to complete trips over two weekends, one weekend with DRL and the other without DRL. Recruitment was specifically targeted toward cyclists who expressed discomfort riding in traffic. Data were collected using a front forward facing camera, GPS, and a vehicle lateral passing distance sensor mounted on the bicycle and a Empatica E4 wrist band (providing physiological data such as electrodermal activity; EDA) worn by the cyclist. Data from those sources were cleaned, processed, merged, and aggregated into time windows depicting car passing and no car passing events. Mixed effects models were used to study the cyclists' skin conductance response (phasic EDA) and baseline skin conductance level (tonic EDA). Car passing, parked vehicles, and roads with dashed centerline markings were observed to increase the cyclists stress. The use of DRL had negligible impact on cyclist stress on roads.